DETERMINANTS OF CHILD LABOUR IN INDIA - Mala Parashar; Ashok Sharma; Pandey, Pramod Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Child labour is a dynamic problem of worldwide concern. The eradication of child labour is major social development goal needs to be achieved by India. This study is an attempt to discuss various factors which affects child labour, such as poverty rate, population, male literacy, female literacy, school drop-out rate, fertility rate, urbanization rate, and per capita state domestic product. In the present study the Census data for the year 2001 & 2011, along with the RBI data on per capita state domestic product for the same years have been used. The number of child workers in a state has shown a decline from 2001 to 2011. Huge state level variation in the number can be seen in study